The Effect of Pressure on the Manufacturing Process of Composites Made from Candlenut Shells and Candlenut Shell Charcoal/Epoxy on Density and Microstructure - gustio mitro; Perdana, Mastariyanto; Pratiwi, Putri (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2024)
Candlenut shell waste has not been widely utilized, especially in the field of material technology. In this study, innovation was carried out on the management of candlenut shell waste with the aim of reducing candlenut shell waste into something useful as a composite of candlenut shell/epoxy. Candlenut shells are ground into powder and sieved on the powder with a mesh of 50-80 with a powder size of 177-297µm. To obtain shell charcoal powder, candlenut shells are carbonized after that ground into powder and sieved with a mesh of 100-200 with a powder size of 74-149µm. While for epoxy resin, it is mixed with a ratio of resin to hardener (2:1). The mixture ratio of candlenut shell composite%, candlenut shell charcoal%, and epoxy resin% is (45:10:45). The printing of the test sample used the printing method, the mold was pressed with a pressure of 21 kg/cm2, 25 kg/cm2, 28 kg/cm2, 32 kg/cm2, 35 kg/cm2 for 24 hours. The sample testing in this study was observation of the microstructure and density testing. In the density test and observation of the microstructure, where the best pressure among the other pressures was at a pressure of 32 kg/cm2 because it can be seen from the density value of 1.14????????/????????3 and the relative density result value of 87%. The things that affect the density test and observation of the microstructure are the comparison at each pressure, the increase in pressure that produces a composite with good physical properties, namely the results of the density data prove an increase in its density and observations of its microstructure prove an increase in the density of the good powder particle composite.